Comparative Analysis of Value-Added Analysis at Five Dadiah Agro-industry Centers in West Sumatra Province - Nurul, Nurul Hathiqah; Kurnia Harlina Dewi; Rina Yenrina (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This study aims to compare the value added of buffalo milk processing production into Dadiah at each Dadiah agro-industry center in West Sumatra Province. The research was conducted in five Dadiah agro-industry centers in West Sumatra Province: Agam District, Lima Puluh Kota District, Tanah Datar District, Sijunjung District, and Solok District. The research was conducted in March-July 2022. The research method used is a case study. Respondents in this study were Dadiah entrepreneurs with owner status. The number of respondents in the survey was 31 Dadiah business actors, with respondent criteria The value added analyzed is Dadiah business actors who process high buffalo milk raw materials in each district. Data analysis using the Hayami method. The results showed that in the production of buffalo milk processing into Dadiah the value-added ratio of Dadiah agroindustry in Sijunjung District was 89.83. higher than the value-added ratio of another dadiah agroindustry in West Sumatra Province. Dadiah processing production in every agroindustry in West Sumatra Province provides a high level of profit found in dadiah agroindustry in Sijunjung District. With a profit rate of IDR 69,948.25/Month, higher than other Dadiah agroindustry in West Sumatra Province.